Medical Gerontology, Review - Skliarenko, Sophio; Tkeshelashvili, Vasil (Caucasus Journal of Health Sciences and Public Health, 2018)
Gerontology is the study of the aging processes and individuals as they grow from middle age through later life. This is the study of older persons. Populations are aging worldwide. This means that people are living longer, and the number of older persons is increasing. These trends are evident in American society, as well as in many countries around the world. In the U.S. the growth of the elderly population will continue into the future. By the middle of the 21st century, one in five Americans will be over 65, and there will be 15 to 18 million persons over the age of 85. These growth trends will result in a demand for professionals with knowledge and expertise in aging. Healthy ageing is the process of slowing down physically and cognitively while resiliently adapting and compensating in order to optimally function and participate in all areas of life. Gerontology studies physical and pathological changes in the ageing population. During ageing process the changes occur in all organs and systems. The main milestone is to gradually adapt to the body changes and maintain healthy ageing.